A Journey About the Innovations of Muslims in Andalusia: رحلة قصيرة عن مبتكرات المسلمين في الأندلس (316هـ/928 – 422هـ/1031م) - Mousa, Faraj Murajia; Abdul Hamid, Ahmad Faisal; Mohd Nor, Mohd Roslan (Journal Al-Muqaddimah, 2022)
This study aims to highlight the chemical innovations of Muslim scholars in Andalusia at the time of the Umayyad Caliphate (316 AH / 928 AD - 422 AH / 1031 AD). Through chemical compounds, and based on the foregoing, the importance of this study is highlighted in the concept of the science of experience, which was discovered and invented by Muslim scholars by mixing chemical compounds. It also has historical importance in the openness of Islam to the world and its coexistence with non-Muslims. The study showed that Muslim scholars were the world’s masters in the science of chemistry, and they contributed to laying the foundations of the science of experience. This study also shows that Muslim scholars were the first to innovate the manufacture of glass and gunpowder and contributed to the development of the paper industry. nitric and sulfuric acid, and they were able to develop potassium, sodium carbonate and gold water, and they were able to extract mercury and for iron ore and copper, they also extracted antimony, arsenic, and other modern innovations that contributed to the chemical industries in Andalusia.